Rosuvastatin revert memory impairment and anxiogenic-like effect in mice infected with the chronic ME-49 strain of Toxoplasma gondii - Evangelista, Fernanda Ferreira; Costa-Ferreira, Willian [UNESP]; Mantelo, Francini Martini; Beletini, Lucimara Fátima; de Souza, Amanda Hinobu; de Laet Sant’Ana, Priscilla; de Lima, Keller Karla; Crestani, Carlos Cesar [UNESP]; Falavigna-Guilherme, Ana Lúcia (Public Library of Science (PLoS), 2021)
The aim of this study was to investigate the effect of rosuvastatin treatment on memory impairment, and anxiogenic-like effects in mice chronically infected with Toxoplasma gondii. For this, Balb/c mice were infected orally with chronic ME-49 strain of Toxoplasma gondii. Oral treatment with rosuvastatin (40mg/kg/day) started on the 51st day post-infection and was performed daily for 21 days. After completion of treatment, anxiety-like effects and locomotion were investigated in the open field (OF) test, whereas novel object recognition (NOR) test was used for evaluation of short- and long-term memory. At the end of the experiments, the brain was collected for Toxoplasma gondii DNA quantification and histopathological analysis. Infection with ME-49 strain decreased the time spent in the center of OF, indicating an anxiogenic effect, without affecting total and peripheral locomotion. Rosuvastatin treatment inhibited the change in the center time. Besides, pharmacological treatment increased total and central locomotion in both non-infected and infected animals. Infection also impaired both short- and long-term memory in the NOR test, and these effects were reverted by rosuvastatin treatment. In addition to effects in behavioral changes, rosuvastatin also reduced parasite load in the brain and attenuated signs of brain inflammation such as perivascular cuffs, inflammatory cell infiltration and tissue damage. These findings indicate for the first time the efficacy of rosuvastatin in treatment of memory impairment and anxiogenic effect evoked by infection with Toxoplasma gondii. These effects might be mediated by reduced cyst load, which in turn decrease inflammation and damage in the brain.